KORELASI PRESTASI BELAJAR KEWIRAUSAHAAN DAN PRESTASI BELAJAR KEJURUAN OTOMOTIF DENGAN MINAT BERWIRAUSAHA PADA SISWA KELAS XI TKR SMK BHAKTI PRAJA BATANG JAWA TENGAH TAHUN AJARAN 2014/2015 - Prapditta Willianto (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research is to know; (1) The correlation between learning achievements entrepreneurship and vocational learning achievements automotive with entrepreneurship interest , (2) The correlation between entrepreneurship learning achievements with entrepreneurship interest , (3) The correlation between learning achievement automotive with entrepreneurship interest in a student of second grade TKR program at SMK Bhakti Praja, Batang Central Java academic year 2014/2015.This research was carried out in SMK Bhakti Praja Batang, Central Java. This research was carried out on the even semester academic year 2014/2015. The population in this study all students of second grade TKR program totalled 121 students. This research using a sample Random Sampling techniques with guideline calculations Nomogram Harry King and obtained samples as much as 96 students. This type of research is the research of Ex Post Facto. The technique of data collection methods question form and documentation. Data analysis technique using analysis double correlation and analysis simple correlation .Data is collected based on the analysis of the results of research as follows: (1) the analysis of double correlation obtained rcount 0.423 > rchart = 0.199 and Fcount of 10.146 > Fchart 3.09 so that we can conclude that simultaneously there any correlation between positive and significant learning achievements entrepreneurship (X1) and automotive vocational learning achievements (X2) with their respective entrepreneurship interest (Y), (2) simple correlation the analysis obtained rcount 0.405 > rchart 0.199 so that it can be concluded there any correlation between positive and significant learning achievements with their respective entrepreneurship interest , (3) the analysis simple correlation obtained rcount 0.203 > rchart 0.199 so that it can be concluded there any positive correlation and significant between automotive learning achievements with their entrepreneurship interest in second grade TKR program at SMK Bhakti Praja Batang central java academic year 2014/2015.